Production and purification of recombinant bovine osteopontin using Escherichia coli as a Cell Factory - Brijaldo Villamizar, Angela Patricia; Londoño-Méndez, María Camila; Arbeláez Ramírez, Luis Fernando; Rueda, Fabian (Universidad Pedagógica y Tecnológica de Colombia, 2022)
Animal reproduction and improvement programs require the optimization of biotechnological tools capable of favoring reproductive rates in various species. The use of protein additives that improve sperm cryopreservation and in vitro embryo production seems to be an interesting alternative. Osteopontin has been related to the fertilizing potential of the sperm and early embryonic development. The objective of this work was to determine the optimal conditions to produce recombinant Osteopontin (rOPN) by using Escherichia coli as a cell factory. For this, the OPN gene was inserted into an expression vector pET28(a+) inducible by IPTG, with resistance to Kanamycin and a histidine tail (6xHis-tag). The resulting construct was used to transform competent E. coli BL21-Star ™ cells. The transformed colonies were used to produce rOPN-H6 at 20, 30, and 37 °C, testing two concentrations of the inducer IPTG (1.0 and 0.1mM). A purification of rOPN-H6 was performed using imidazole affinity columns (10, 50, 200, 350, 500mM). The results showed that the production of rOPN-H6 was only successful at 37°C regardless of the concentration of IPTG used. Purification of rOPN-H6 was successful using imidazole at 200mM, with an apparent tendency to dimerization after obtaining purified protein. In this way, the best conditions to obtain recombinant OPN is concluded, suggesting its potential use in sperm cryopreservation assays and culture media for in vitro embryo production.